2002
DOI: 10.1016/s0006-3495(02)75504-5
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Release of Calcium Elicited by Membrane Depolarization in Ryanodine-Injected Mouse Skeletal Muscle Fibers

Abstract: The effect of micromolar intracellular levels of ryanodine was tested on the myoplasmic free calcium concentration ([Ca(2+)](i)) measured from a portion of isolated mouse skeletal muscle fibers voltage-clamped at -80 mV. When ryanodine-injected fibers were transiently depolarized to 0 mV, the early decay phase of [Ca(2+)](i) upon membrane repolarization was followed by a steady elevated [Ca(2+)](i) level. This effect could be qualitatively well simulated, assuming that ryanodine binds to release channels that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…This Ca 2+ transient depression was accompanied by a progressive increase in resting Ca 2+ , due to a steady elevated level following the Ca 2+ transient decay phase following repolarization. These results were indicative of an open-locked state for the RyR in situ, a feature consistent with a usedependence effect [17]. Conversely, a higher ryanodine concentration (100 µM) than the one used in the present study was found to induce a "modest increase" of the voltage-activated Ca 2+ transients in crayfish muscle fibers, which reflects the complexity of ryanodine actions at low and high concentration [28].…”
Section: Discussionsupporting
confidence: 83%
“…This Ca 2+ transient depression was accompanied by a progressive increase in resting Ca 2+ , due to a steady elevated level following the Ca 2+ transient decay phase following repolarization. These results were indicative of an open-locked state for the RyR in situ, a feature consistent with a usedependence effect [17]. Conversely, a higher ryanodine concentration (100 µM) than the one used in the present study was found to induce a "modest increase" of the voltage-activated Ca 2+ transients in crayfish muscle fibers, which reflects the complexity of ryanodine actions at low and high concentration [28].…”
Section: Discussionsupporting
confidence: 83%
“…Mice were killed by cervical dislocation before removal of the muscles. Procedures for enzymatic isolation of single muscle fibres, partial insulation of the fibres with silicone grease and intracellular microinjection were as previously described (Jacquemond, 1997; Collet et al 1999, 2004; Collet & Jacquemond, 2002). In brief, the major part of a single fibre was electrically insulated with silicone grease so that whole‐cell voltage‐clamp could be achieved on a short portion of the fibre extremity.…”
Section: Methodsmentioning
confidence: 99%
“…For these, the solution that was microinjected in the fibres also contained 1 m m of either indo‐1 or fluo‐3. The optical set‐up and the procedures used for the indo‐1 fluorescence measurements were as previously described (Jacquemond, 1997; Collet et al 1999; Collet & Jacquemond, 2002; Pouvreau et al 2004). In brief, a Nikon Diaphot epifluorescence microscope was used in diafluorescence mode.…”
Section: Methodsmentioning
confidence: 99%
“…Procedures for enzymatic isolation of single fibres, partial insulation of the fibres with silicone grease and intracellular dye loading were as previously described [5,7,8,19]. In brief, mice were killed by cervical dislocation after halothane (Sigma Aldrich, Saint Quentin Fallavier, France) inhalation, before removal of the muscles.…”
Section: Isolation and Preparation Of Fdb Muscle Fibresmentioning
confidence: 99%
“…Results were either expressed in terms of indo-1% saturation or in actual free Ca 2+ concentration (for details of calculation, see [10,19]). In vivo values for R min , R max and β were measured using procedures previously described [5,7]. Corresponding mean values measured in control and Cav-3 P104L -expressing fibres were 0.33±0.09, 1.29±0.15, 2.79±0.11 (n=8) and 0.31±0.12, 1.31±0.14, 2.84±0.10 (n=7), respectively.…”
Section: Calibration Of the Indo-1 Response And [Ca 2+ ] Intra Calculmentioning
confidence: 99%